Digital Divide and Operational Digital Literacy in Deaf and Hard-of-Hearing Students - Krasavina, Yulia; Ponomarenko, Ekaterina; Shishkina, Anastasia; Gareyev, Andrey (Specijalna edukacija i rehabilitacija, 2025)
Introduction. The digital divide is a concept that has been explained as deficiencies in accessing and mastering new technologies caused by economic, social, or personal reasons. Overcoming the digital divide is a crucial social issue that implies focused research on digital literacy in the most vulnerable groups. Objectives. This study is aimed at assessing operational digital literacy in deaf and hard-of-hearing (DHH) university students and revealing potential grounds for hearing disability digital divide. Methods. The selection of study participants involved purposive sampling. Qualitative data on learning experiences in digital media were collected through verbal protocol sessions, diary entries, and semi-structured interviews with DHH university students. Grounded theory (open and axial coding) was used to analyse the data collected during interviews and verbal protocol sessions. Data collected from diary entries were analysed with Voyant Tools. Results. The main findings were categorised into: the use of the Internet and mobile applications, the digital divide, the use of text editors and spreadsheet programs, document creation and editing, and Internet search. The digital divide phenomenon in DHH students was described through the causal paradigm model. Conclusions. The study clarifies the difficulties that DHH participants faced in every stage of completing experimental tasks in the digital environment and provides arguments for proving that the grounds for the hearing disability digital divide are rooted in the lack of reading, writing, and written communication skills and not technical skills. The study also revealed the students’ ‘survival’ strategies to overcome difficulties with poor reading skills and perceiving auditory information.